XBi4S7 (X = Mn, Fe): New Cost‐Efficient Layered n‐Type Thermoelectric Sulfides with Ultralow Thermal Conductivity. (18th September 2019) - Labégorre, Jean‐Baptiste; Virfeu, Agathe; Bourhim, Abdelhamid; Willeman, Héloïse; Barbier, Tristan; Appert, Florian; Juraszek, Jean; Malaman, Bernard; Huguenot, Arthur; Gautier, Régis; Nassif, Vivian; Lemoine, Pierric; et al.
Abstract: A new class of cost‐efficient n ‐type thermoelectric sulfides with a layered structure is reported, namely MnBi4 S7 and FeBi4 S7 . Theoretical calculations combined with synchrotron X‐ray/neutron diffraction analyses reveal the origin of their electronic and thermal properties. The complex low‐symmetry monoclinic crystal structure generates an electronic band structure with a mixture of heavy and light bands near the conduction band edge, as well as vibrational properties favorable for high thermoelectric performance. The low thermal conductivity can be attributed to the complex layered crystal structure and to the existence of the lone pair of electrons in Bi 3+ . This feature combined with the relatively high power factor lead to a figure of merit as high as 0.21 (700 K) in undoped MnBi4 S7, making this material a promising n ‐type candidate for low‐ and intermediate‐temperature thermoelectric applications. Abstract : Ultralow thermal conductivity is reported in new cost‐efficient n ‐type layered XBi4 S7 (X = Mn, Fe) thermoelectric materials. The complex layered crystal structure, exhibiting a multiband electronic structure and ultralow thermal conductivity, favors high thermoelectric performance.